3-YEAR FOLLOW-UP OF REGENERATIVE ENDODONTIC TREATMENTS WITH THE APPLICATION OF CONCENTRATED GROWTH FACTOR AS SCAFFOLD: NINE CASES - Gok, Tuba (My University, 2023)
The aim of this case series is to present Three year clinical and radiographic follow-ups of nine regenerative endodontic treatment cases using concentrated growth factor in necrotic immature permanent teeth. Nine patients aged 8-21 years were referred to our clinic. According to clinical and radiographic examinations, it was decided to perform RET. After the working length determination, teeth were irrigated with 2.5% NaOCl and activated with Endo Activator. Root canals were instrumented with XP-endo Finisher-R file. 20 mL of 17% EDTA was used as final irrigation, and calcium hydroxide and temporary fillings were placed. Two weeks later, roots were irrigated with 17% EDTA and five mL distilled water and dried with paper points. Bleeding was induced into the coronal part of the root canal. Concentrated growth factor (obtained from the patient’s blood) was placed into the root canals. Biodentine was placed on the blood clot and permanent restorations were made with resin composite. At three-year follow-up, clinical and radiographic healing was observed in five patients. In the other four patients, persistent infection and sinus-tract formation were detected at different time periods. Although RET is a promising treatment that aims to preserve teeth vitally, more randomized clinical research is needed due to its unpredictable results.
Keywords: Regenerative endodontic treatment; Concentrated growth factor; immature ne- crotic permanent tooth